PENELITIAN KARAKTERISTIK AERODINAMIKA SAVONIUS BERSUDU BANYAK DENGAN METODA PENGGESERAN MESH - Aribowo, Agus (Indonesian Journal of Aerospace, 2006)
Rotation of Savonius blades could be simulated using Sliding Mesh methode. The effective solution can be obtained by interfacing between moving zone and fixed zone by coordinating the linked cell. The number of tested blades 2,3,4 and 6. The result is the Savonius turbine with 3 blades having torque coefficient higher and efficiency level the compared which the other blades. The spacing of blade axis make airflow infiltrate and causing increase of force momen and negative drag force. By increasing the number of blades will result in the reduction of negative and positive force between one blade to the other. As a result, the performance will be reduced due to the increased number of blades.